High-temperature oxidation-resistant NiCr/Al duplex coating on carbon steel substrate - Cuong, Ly Quoc; Tuan, Nguyen Van; Ha, Pham Thi; Ly, Pham Thi; Quan, Vo An; Thuy, Dao Bich; Anh, Nguyen Tuan; Quy, Le Thu (Vietnam Journal of Science and Technology, 2020)
The oxidation resistance property of NiCr/Al duplex coating system has been evaluated at 800oC during retention times of 1.5; 3; 4.5 and 6 hours. After the oxidation test, SEM-EDS data indicated the diffusion of aluminum into the NiCr coating, whereas XRD patterns revealed the appearance of new phases (Al3Ni2, Al2O3). In addition, an increase in micro-hardness (up to 518 - 842 Hv) was obtained after oxidation test. These obtained findings indicated that NiCr/Al coating had higher oxidation resistance than NiCr coating.